Worldwide drinking water occurrence and levels of newly-identified perfluoroalkyl and polyfluoroalkyl substances - Kaboré, Hermann A.; Vo Duy, Sung; Munoz, Gabriel; Méité, Ladji; Desrosiers, Mélanie; Liu, Jinxia; Sory, Traoré Karim; Sauvé, Sébastien (The Science of the total environment, 2018)
•133 PFASs from different chemical classes were screened in drinking water samples.•Detection frequencies in tap water were high (64–92%) for short-chain PFCAs/PFSAs.•PFOS and PFOA did not exceed 5ngL−1 across the 97 samples surveyed.•2 tap water samples from Burkina Faso showed high 5:3FTCA levels (landfill sources).•First report of a cyclic PFSA (PFECHS) and C4–C6 FASAs (FBSA, FHxSA) in drinking water. [Display omitted] In the last decade or so, concerns have arisen with respect to the widespread occurrence of perfluoroalkyl acids (PFAAs) in the environment, food, drinking water, and humans. In this study, the occurrence and levels of a large range of perfluoroalkyl and polyfluoroalkyl substances (PFASs) were investigated in drinking water (bottled and tap water samples) from various locations around the world. Automated off-line solid phase extraction followed by ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry was used to analyze PFASs of various chain lengths and functional groups. In total, 29 target and 104 suspect-target PFASs were screened in drinking water samples (n=97) from Canada and other countries (Burkina Faso, Chile, Ivory Coast, France, Japan, Mexico, Norway, and the USA) in 2015–2016. Out of the 29 PFASs quantitatively analyzed, perfluorocarboxylates (PFCAs: C4/14), perfluoroalkane sulfonates (PFSAs: C4, C6, C8), and perfluoroalkyl acid precursors (e.g., 5:3 fluorotelomer carboxylate (5:3 FTCA)) were recurrently detected in drinking water samples (concentration range: <LOD to 39ngL−1). Tap water samples from Canada showed noteworthy differences depending on their source; for instance, ∑29PFASwas significantly greater in those produced from the Great Lakes/St. Lawrence River ecosystem than those produced from other types of sources (14 versus 5.3ngL−1, respectively). A suspect-target screening approach indicated that other perfluoroalkane sulfonamides (FBSA, FHxSA), perfluoroethyl cyclohexane sulfonate (PFECHS), ultrashort chain (C2–C3) PFSAs (PFEtS, PFPrS), and two additional PFSAs (PFPeS (C5) and PFHpS (C7)) were repeatedly present in tap water samples (concentration ranges: <LOD to 4.0ngL−1). To the authors' best knowledge, this constitutes the first observation of a cyclic perfluoroalkane sulfonate (PFECHS) and C4–C6 perfluoroalkane sulfonamides (FBSA, FHxSA) in drinking water. According to the newly updated US EPA health advisory for PFOS and PFOA (70ngL−1), the drinking water samples collected in the present monitoring would not pose a health risk to consumers as regards PFAA levels.